Forest Moratorium Policy, Deforestation and Forest Degradation in Papua Province - R Aditya Yudhanegara (Universitas Muhammadiyah Mataram, 2021)
On May 20, 2011, the government of the Republic of Indonesia enacted Presidential Instruction (Inpres) number 10 of 2011 as the start of the forest moratorium policy. This policy aimed to reduce the rate of deforestation and forest degradation through a moratorium on the issuance of new permits. However, the effectiveness of this policy in achieving these goals is still being debated. This study shows that the forest moratorium policy has successfully reduced the extent of the concession area, as well as the average deforestation and forest degradation rate in Papua Province. However, the concession extent was not directly proportional to the rate of deforestation and forest degradation in the concession area, and the decline of the average rate of deforestation and forest degradation was not accompanied by a steady rate during the enactment of the policy. This study also reveals that policy implementation at the provincial level was hampered by the communication factor, the resources factor, and the disposition factor. We recommend that, besides limiting the concession area, the government should improve the licensing governance by strengthening the monitoring and evaluation, as well as the mechanism of business-work-plan approval. Also, the central government should improve coordination with the local government to overcome factors hampering the implementation of the moratorium policy.